PERSPEKTIF PELESTARIAN LINGKUNGAN HIDUP DALAM ISLAM - M. Syakur Sf. (MEDIAGRO, 2008)
Promoting and appreciating Islamic religious spirituality is a condition sine qua non to keep its strength equal to that of  natural law, economic law, and market mechanism over which  none and no system could control. Nonetheless, leaving the  economic law and market mechanism prevail uncontrolled is not  an Islamic attitude of religious behavior. Authentic religious attitude and way of life must be prophetic and trans-formative in nature and manifested in the practical  action of watching and controlling the development of the  natural law and economic law themselves. Otherwise, human  beings could be subordinated and co-opted by the natural law.  Indeed,  having  firm religious traditions, Muslim communities are  exercised to plead themselves from the shackling routines of daily life. There has to be a serious and  continuous effort to understand fundamental and functional meaning of formal rituals of Islam, in such a way that Islam supports not  only Theo-centric  but also socio-economic concerns. Once Islam is shackled by its  routines and finds no alternative interpretation of its rituals,  there hardly is hope of important contributions made by Islamic scholars to cope with ecological and global crises. Kata-Kata Kunci: Lingkungan, Pembangunan, Etika dan Spiritual